Seventh Plan 1985-90 and Annual Plan 1985-86 Orissa (Draft) Volume. I Government of Orissa, Planning and Co-ordination Department, Bhubaneswar - Planning Commission (Planning Commission, 1984)
Since the inception of First Five-Year Plan, the State plans in Orissa have followed the National objectives of growth, equity and social justice, self-reliance, improved efficiency and productivity. the progress so far achieved has been substantial though the pace has been somewhat slower than envisaged. the very process of development has, however, generated new impulses for acceleration. 1.2. With an estimated population of 2.64 crores in 1980-81, Orissa accounts for about 3.85 percent of the country’s population. The economy of the State is basically agrarian. 60.9 per cent of the State Domestic Product originates from the agriculture and allied sector which also accounts for 80.34 per cent of the total work force in the State. At the national level, on the other hand, the agriculture and allied sector contributes 39.5 per cent of the National Domestic Product and 72.56 per cent of the work force.
Government of Orissa, Planning and Co-ordination Department, Bhubaneswar